2014
DOI: 10.1111/tmi.12254
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of a hand washing intervention on health outcomes and school absence using a randomised trial in Indian urban communities

Abstract: Abstractobjectives To evaluate how an intervention, which combined hand washing promotion aimed at 5-year-olds with provision of free soap, affected illnesses among the children and their families and children's school absenteeism.methods We monitored illnesses, including diarrhoea and acute respiratory infections (ARIs), school absences and soap consumption for 41 weeks in 70 low-income communities in Mumbai, India (35 communities per arm).results Outcomes from 847 intervention households (containing 847 5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 21 publications
0
113
0
1
Order By: Relevance
“…All 12 trials in this group were randomized by cluster using primary schools (Bowen 2004 CHN; Talaat 2008 EGY; Pickering 2013 KEN), day-care centres (Black 1977 USA; Bartlett 1984 USA; Butz 1990 USA; Roberts 1996 AUS; Carabin 1997 CAN; Ladegaard 1999 DEN; Kotch 2003 USA; Zomer 2012 NED ), or classrooms in day-care centres (Kotch 1989 USA) as the unit of randomization. These trials were all conducted in high-income countries except for three trials conducted in LMICs Bowen 2004 CHN, (which was undertaken in Fujian province in China) Talaat 2008 EGY (which was conducted in Cairo, Egypt), and Pickering 2013 KEN (conducted in Nairobi, Kenya).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 12 trials in this group were randomized by cluster using primary schools (Bowen 2004 CHN; Talaat 2008 EGY; Pickering 2013 KEN), day-care centres (Black 1977 USA; Bartlett 1984 USA; Butz 1990 USA; Roberts 1996 AUS; Carabin 1997 CAN; Ladegaard 1999 DEN; Kotch 2003 USA; Zomer 2012 NED ), or classrooms in day-care centres (Kotch 1989 USA) as the unit of randomization. These trials were all conducted in high-income countries except for three trials conducted in LMICs Bowen 2004 CHN, (which was undertaken in Fujian province in China) Talaat 2008 EGY (which was conducted in Cairo, Egypt), and Pickering 2013 KEN (conducted in Nairobi, Kenya).…”
Section: Resultsmentioning
confidence: 99%
“…Only two trials reported this statistic: one community-based trial, Luby 2003b PAK, and one trial in a child day-care centre, Roberts 1996 AUS. We assumed that these ICC estimates could be generalized to other community-based and child day-care centre or school-based trials respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This was similar to findings by Nicolson et al reported in 2014. 34 While around 6% children were reportedly practicing open defecation. Open defecation poses a serious threat to children's health and is the leading cause of diarrhoea related mortality in children.…”
mentioning
confidence: 99%
“…There are many studies showing that specifically the improvement of handwashing is decreasing substantially the diarrhea morbidity [3][4][5][6][7]. The handwashing is one of the primary prevention not only from the oral fecal diseases but also from the respiratory infected diseases [4,6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%